2022
DOI: 10.21107/jk.v14i3.9042
|View full text |Cite
|
Sign up to set email alerts
|

KEANEKARAGAMAN SPESIES DAN KARAKTERISTIK HABITAT KERANG KIMA (Cardiidae: Tridacninae) DI EKOSISTEM INTERTIDAL TANJUNG BILIK TAMAN NASIONAL BALURAN

Abstract: Kima (Giant clam) is a group of sea shells that belongs to the cardiidae family and the Bivalvia class. Kima is one of the international trade commodities with high economic value. This heterogeneous habitat condition is interesting to study, especially in order to understand the habitat characteristics and species diversity of clams in the intertidal zone of the Baluran National Park chambers. To determine the characteristics of the habitat selected by the clam shell population and species diversity, a road s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
1
3
0
5
Order By: Relevance
“…The absence of H. Hippopus in Morella waters could be attributed to the substrate in this location which is predominantly by massive coral while in Suli waters predominant substrate is sand where H. Hippopus was found. Previous studies showed that H. Hippopus only found in the sand substrate [16,17]. Species composition and the number of species found in this Ambon Island waters is similar to the giant clams found in Tanjung Bilik, Baluran National Park [17] but lesser than the number of species in Kei Island (5 species) [7] and Kei Kecil waters (6 species) [18].…”
Section: Species Composition Of Giant Clamssupporting
confidence: 69%
See 1 more Smart Citation
“…The absence of H. Hippopus in Morella waters could be attributed to the substrate in this location which is predominantly by massive coral while in Suli waters predominant substrate is sand where H. Hippopus was found. Previous studies showed that H. Hippopus only found in the sand substrate [16,17]. Species composition and the number of species found in this Ambon Island waters is similar to the giant clams found in Tanjung Bilik, Baluran National Park [17] but lesser than the number of species in Kei Island (5 species) [7] and Kei Kecil waters (6 species) [18].…”
Section: Species Composition Of Giant Clamssupporting
confidence: 69%
“…Previous studies showed that H. Hippopus only found in the sand substrate [16,17]. Species composition and the number of species found in this Ambon Island waters is similar to the giant clams found in Tanjung Bilik, Baluran National Park [17] but lesser than the number of species in Kei Island (5 species) [7] and Kei Kecil waters (6 species) [18]. The species absence compared to Kei Island is T. noae while to Kei Kecil are T. derasa and T. gigas.…”
Section: Species Composition Of Giant Clamsmentioning
confidence: 98%
“…Di beberapa frame foto juga ditemukan kima atau Tridacna sp. Keberadaan kima yang terdapat pada Pantai Balekambang merupakan mikroba indikator pencemaran lingkungan, yang menunjukkan bahwa meskipun aktivitas antropogenik cenderung mengganggu keberadaan terumbu karang, tetapi kondisi kejernihan air laut tetap terjaga dan terbebas dari bahan pencemar (polutan) (Setiawan et al, 2022).…”
Section: Susunan Karang Keseluruhanunclassified
“…Pulau Talam merupakan pulau yang jauh dari pemukiman sehingga sangat mendukung pernyataan Elfwing et al dalam Setiawan et al (2021) yaitu kima sangat rentan terhadap perubahan lingkungan dan memilih habitat dengan kondisi air laut yang jernih dan bebas dari pencemaran di wilayah intertidal maupun subtidal. Adapula bulu babi merupakan organisme yang dapat hidup berdampingan dengan terumbu karang tanpa menimbulkan kerugian, tetapi dengan meningkatnya populasi bulu babi akan mempengaruhi terumbu karang yang dapat mengakibatkan kematian karang muda (COREMAP LIPI dalam Bangapadang, 2019).…”
Section: Kepadatan Megabentosunclassified